Remote non-pharmacologic interventions for sleep problems in healthcare workers during the COVID-19 pandemic - Torrente, Fernando Manuel (2021)
Objectives: This is a protocol for a Cochrane Review (intervention). The objectives are as follows:. To assess the effects of remote non-pharmacologic interventions, compared with other specific intervention, non-intervention or alternative intervention for sleep problems in in healthcare workers during the coronavirus disease 2019 outbreak.